According to Masonic Sources, the Events of Dissolution and Division Experienced by the Masons of Türkiye During the Republican Period - Enver Emre Öcal (Yakın Dönem Türkiye Araştırmaları)
Freemasonry began to spread within the Ottoman Empire in the 18th century, initially operating under the authority of foreign obediences. This structure underwent a significant transformation following the 1908 Revolution, which led to the establishment of the Ottoman Mashriq-ı Azam and Supreme Council for the first time. Freemasonry continued in this form until the Republican era, during which it faced pivotal events such as the “Put to Sleep” and the “Great Schism.”This article aims to trace the historical development of Freemasonry from the Ottoman Empire to the Republic of Türkiye and to provide a detailed analysisof the significant events that occurred during the Republican period. Using primary sources such as the minutes of the Grand National Assembly of Türkiye, archival documents, and Masonic publications from both Türkiye and abroad, the study focuses on the developments within Turkish Freemasonry after 1965. By examining this underexplored topic within the context of the international recognition practices of Turkish Freemasons, the article seeks to provide a comprehensive understanding of the challenges and transformations experienced by Freemasonry in Türkiye.